Integrating Coffee and Biofloc for Regional Economy with Bank of Indonesia - Ruly Ahsanul Hakim; Nabiela Rizki Alifa; Akbar Riskal Amani (Faculty of Islamic Economics and Business, Madura Islamic State University, 2026)
Purpose – This study aims to analyze the role of Bank Indonesia in strengthening the real sector and supporting regional economic growth through the optimization of local potential, particularly through the integration of coffee cluster development and pesantren-based fish farming using the biofloc system. Methodology – This study uses a qualitative descriptive approach based on literature studies and internship results to describe in depth the implementation of the Bank Indonesia Tasikmalaya program. Findings – The results of the study show that Bank Indonesia's facilitation has succeeded in increasing the competitiveness of coffee MSMEs in the East Priangan region such as Kopi Bunar, Kopi Cigalontang, and Tenjo Bumi Kopi as well as encouraging the implementation of an efficient, environmentally friendly biofloc system in Islamic boarding schools, which contributes to local food security. Implications – This initiative has strategic implications for strengthening the real sector and developing a sharia-based economy. In addition, this program can serve as a model for collaboration between financial institutions, MSMEs, and Islamic educational institutions in realizing inclusive sustainable development. Originality – This study offers a new perspective by highlighting the synergy between coffee cluster development and biofloc cultivation in Islamic boarding schools as a model for real sector integration based on sharia economic values and environmental sustainability.